(untitled) (The International Journal for Scientific Research, 2026)
This study aims to explore how the concept of gender is constructed through textbooks, which shapes a child’s upbringing and the formation of their masculine and feminine identities, enabling them to interact and adapt to their social context. It involves studying and analyzing the content of an Arabic language textbook for the third grade of primary school to determine the nature of the representations conveyed within it, and whether the stereotypes reflect gender inequality or present new images based on fairness, equality, and mutual cooperation.